2018
DOI: 10.1038/bjc.2017.467
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory markers have independent prognostic value in patients with metastatic testicular germ cell tumours undergoing first-line chemotherapy

Abstract: Systemic inflammatory markers might have prognostic utility for patients with metastatic GCT. The planned IGCCCG update could be an opportunity to test these markers in a larger data set.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 35 publications
(40 reference statements)
4
61
2
2
Order By: Relevance
“…This tool recognized never relapsing and never dying patients and identified a poor prognostic group, where none of the relapsed patients were salvageable with treatment (Chovanec et al ., ,,). Simultaneously, Fankhauser et al ., () reported the same findings on SII together with the prognostic significance of neutrophils, neutrophil‐to‐lymphocyte ratio and c‐reactive protein.…”
Section: Emerging Immune Biomarkers and Immunotherapy In Gctssupporting
confidence: 61%
“…This tool recognized never relapsing and never dying patients and identified a poor prognostic group, where none of the relapsed patients were salvageable with treatment (Chovanec et al ., ,,). Simultaneously, Fankhauser et al ., () reported the same findings on SII together with the prognostic significance of neutrophils, neutrophil‐to‐lymphocyte ratio and c‐reactive protein.…”
Section: Emerging Immune Biomarkers and Immunotherapy In Gctssupporting
confidence: 61%
“…In this issue of the British Journal of Cancer, two articles highlight for the first time the prognostic significance of SII in patients with GCT. Fankhauser et al (2018) evaluated the prognostic value of SII in patients with metastatic GCT treated with cisplatin-based chemotherapy. The neutrophilto-lymphocyte ratio (NLR) was also calculated.…”
mentioning
confidence: 99%
“…Recent studies have shown that the systemic inflammatory response can induce malignant tumor behavior and lead to shorter survival durations in patients with malignant solid tumors, and can also predict the prognosis of cancer (18)(19)(20)(21). SII as a novel systemic immune-inflammation index, that represents the overall inflammatory, and immune status of the patient has proven to be a meaningful preoperative biomarker in various tumors (18,(20)(21)(22). Hu et al found that in hepatocellular carcinoma SII was associated with circulating tumor cell levels and local recurrence (21), while Wang et al noted that SII was associated with age, tumor invasion, local lymph node metastasis, and distant metastasis in gastric cancer (18).…”
Section: Discussionmentioning
confidence: 99%